2016
DOI: 10.3347/kjp.2016.54.2.133
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Protein Arginine Methyltransferase 5 as a Regulator for Encystation of <i>Acanthamoeba</i>

Abstract: Encystation is an essential process for Acanthamoeba survival under nutrient-limiting conditions and exposure to drugs. The expression of several genes has been observed to increase or decrease during encystation. Epigenetic processes involved in regulation of gene expression have been shown to play a role in several pathogenic parasites. In the present study, we identified the protein arginine methyltransferase 5 (PRMT5), a known epigenetic regulator, in Acanthamoeba castellanii. PRMT5 of A. castellanii (AcPR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…AcPRMT1 was localized both in the cytoplasm and the nucleus (Fig. 3), while we have previously identified that AcPRMT5 was localized mainly in the nucleus [19]. However, the substrates of PRMT1 and PRMT5 of A. castellanii have yet to be identified.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…AcPRMT1 was localized both in the cytoplasm and the nucleus (Fig. 3), while we have previously identified that AcPRMT5 was localized mainly in the nucleus [19]. However, the substrates of PRMT1 and PRMT5 of A. castellanii have yet to be identified.…”
Section: Discussionmentioning
confidence: 92%
“…2 ). The previously identified PRMT5 of A. castellanii (AcPRMT5) also showed increased expression patterns during encystation [ 19 ]. However, AcPRMT1 was expressed higher than AcPRMT5 during encystation of A. castellanii ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Geyer et al [ 15 ] have shown evidence of cytosine methylation in Schistosoma mansoni , suggesting the presence of a functional DNA methylation machinery. However, methylated cytosine and DNA methyltransferase have not been reported in Acanthamoeba yet, although protein arginine methyltransferase 5 has been identified [ 16 ].…”
Section: Introductionmentioning
confidence: 99%